Morphological effects of chemotherapy on ovarian carcinoma. Issue 1 (1st January 2002) - McCluggage, W G; Lyness, R W; Atkinson, R J; Dobbs, S P; Harley, I; McClelland, H R; Price, J H
Abstract : Aims: Traditionally, advanced stage ovarian carcinoma is treated by debulking surgery followed by chemotherapy. However, in some circumstances preoperative chemotherapy may be given before optimal surgical debulking. This study aims to describe the morphological features found in ovarian carcinoma after chemotherapy because these have not been detailed previously. Methods: Histological sections were examined from 18 cases of ovarian carcinoma that had been treated by preoperative chemotherapy. The morphology was compared with any pre-chemotherapy biopsies that had been performed. Tumours were classified as showing morphological features suggesting a good response to chemotherapy (n = 14) or as showing little or no response (n = 4). Serum CA125 values before and after chemotherapy were compared. In all cases, the mitotic activity index (MAI), volume percentage of epithelium (VPE), and mean nuclear area (MNA) of tumour cells were calculated. Results: The preoperative biopsies were all typical ovarian serous or endometrioid adenocarcinomas. Morphological features present in the group responding to chemotherapy included the presence of small groups or single tumour cells in a densely fibrotic stroma. Tumour cells were characterised by both nuclear and cytoplasmic alteration, making accurate tumour typing and grading impossible. Nuclear features included the presence of bizarre enlargement with hyperchromatism, irregularity of outline, and chromatin clumping or smudging. Cytoplasmic alterations included intense eosinophilia, vacuolation, or foam cell change. There were pronounced stromal changes of fibrosis, inflammation, collections of foamy histiocytes, cholesterol cleft formation, haemosiderin deposition, fat necrosis, and dystrophic calcification, including the presence of many free psammoma bodies. There was no correlation between morphological response and biochemical response, as determined by serum CA125 values. In all nine cases in which pre-chemotherapy and post-chemotherapy biopsies were available, the MNA increased post-chemotherapy (p = 0.007, paired Wilcoxon test) and in six of nine cases the MAI decreased (p = 0.093). Conclusions: Because preoperative chemotherapy is being used increasingly in the management of ovarian cancer, pathologists should be aware of the resultant morphological effects. Accurate tumour typing and grading is impossible. In some cases, it may be difficult to confirm the presence of residual tumour, making it imperative that pre-chemotherapy tissue biopsies are obtained. Definite confirmation of residual tumour may require the examination of multiple histological sections from areas showing pronounced stromal changes, sometimes with multiple levels and immunohistochemistry. In the absence of definite residual tumour, the report should state that the features are consistent with the prior presence of tumour.